ANALISIS PERBANDINGAN PARAMETER DAN PROFIL DOSIS MENGGUNAKAN PHANTOM STANDAR DAN TIDAK STANDAR - Nora Fajria; Wahyu Setia Budi; Zaenal Arifin (Jurusan Fisika, Fakultas Sains dan Matematika, Universitas Diponegoro, 2014)
A study has been conducted to analyze the dose parameters are CTDI100, CTDIw, CTDIvol, DLP and dose profiles by using standard phantom (150 mm) and non-standard phantom (300 mm). This research utilized an abdomen phantom, CT Dose Profiler and software Ocean. Exposure factors in this study in accordance with the conditions of the abdomen routinely performed at the Hospital of the tube voltage 120 kV, current 350 mA, collimation 40 mm, and pitch 1.375. The detector is placed in the center of the phantom and scanning with variation of scan-length 150 mm and 200 mm in the standard phantom (150 mm) and the variation of the scan-length 150 mm, 200 mm, 300 mm in non-standard phantom (300 mm). The result obtained is the parameter dose values in the non-standard phantom (300 mm) are higher than standard phantom (150 mm). At a scan length of 150 mm, the difference in value is 4.825% CTDI100, CTDIw 4.858%, 4.823% CTDIvol, and DLP 4.820%. Meanwhile, the difference in the value of the parameter dose at the scan length of 200 mm is CTDI100 3.477%, 3.494% CTDIw, CTDIvol 3.510%, and DLP 3.512%. The resulting dose profile has similar peak-dose value but have a different width so that the dose profile in non- standard phantom (300 mm) is wider and having higher FWHM value than the standard phantom (150 mm) because non-standard phantom has longer scan length that lead to excessively scattered radiation.Keywords: CT Dose Profiler, dose profiles, scan length, standard phantom, non- standard phantom, CTDI100, CTDIw, CTDIvol, DLP, FWHM.